Assessment of Priorities Model Representation of the Problem of Determining Investment Priorities of the Ukrainian Alternative Energy Industry: Theoretical and Applied Aspect - Osadcha, Natalia; Zaverbnyj, Andrij; Liashenko, Viacheslav (European Journal of Sustainable Development, 2025)
Ukraine’s energy system is in a situation of crisis and development. The system needs stable operation in the face of war and crisis. This requires attracting investments, including foreign ones. To determine the priority areas for investment, it is necessary to model and analyze the benefits and effects of renewable energy types in Ukraine. The aim of the study was to assess the priorities of a model-based representation for determining investment priorities in Ukraine’s alternative energy sector. The study employed methods such as analysis, synthesis, morphological analysis, elements of economic and mathematical modeling, and the "Fuzzy TOPSIS" method. The main results include the calculation of indicators for the normalized evaluation of alternatives (renewable energy stations) to select and rank these stations according to a strategy for prioritizing energy sectors for development in Ukraine. The economic effect of implementing the proposed model for establishing investment priorities in Ukraine’s alternative energy sector lies in the fact that the use of scenario-based evaluation factors primarily encourages an increase in investment inflows, particularly from foreign investors. The transition of Ukraine’s energy system to a carbon-neutral policy will accelerate the country’s path toward sustainable and harmonious development, strengthening Ukraine’s position among countries advancing alternative energy, even under temporary martial law conditions. Keywords: energy, renewable energy, investment climate, threats, war, economic sustainability, energy system, energy strategy, investment, modeling